Yaws' thermophysical properties of chemicals and hydrocarbons - Yaws, Carl L. (Knovel, 2009)
Presents over 7,800 organic and inorganic chemicals, and hydrocarbons. Designed and formatted for field, lab or classroom usage, it provides unparalleled access to invaluable data.
Keywords: Chemistry, Organic.; Inorganic compounds -- Thermal properties.; Hydrocarbons -- Thermal properties.; Thermochemistry.; Chemicals -- Tables.; Hydrocarbons -- Tables.; elektronické knihy; electronic books